Ecosystem Restoration through Landscape Resource Conservation: Lessons Learned from Central India - Anantha, K.H.; Singh, Ramesh; Venkataradha, A.; Garg, K.K.; Ram, Asha; Harawa, Rebbie; Jat, Mangi L. (International Crops Research Institute for the Semi-Arid Tropics, 2025)
This policy brief highlights the outcomes and lessons learned from a landscape restoration initiative focused on dryland management in Central India’s Bundelkhand region. Through integrated and participatory resource management, anchored in the restoration of traditional rainwater harvesting systems and scientific monitoring, the project achieved significant improvements in groundwater recharge, cropping intensity, and rural livelihoods. A key innovation was the revival of the traditional haveli system, which had fallen into disrepair. Introducing an innovative masonry core wall concept and safe water discharge outlets, the restored havelis not only enhanced groundwater recharge but also strengthened a range of ecosystem services and supported productive post-monsoon agriculture, revitalizing previously abandoned lands. The Bundelkhand experience demonstrates that science based, community-driven approaches can address the major challenges of land degradation, water scarcity, and rural poverty in India’s dryland regions. The project calls for scaling similar models nationwide through coordinated, dedicated-funding, and evidence-driven policies. Such efforts would advance the country’s goals for climate adaptation, land degradation neutrality, water security, and rural prosperity.